2017
DOI: 10.1002/rrq.191
|View full text |Cite
|
Sign up to set email alerts
|

Strategy Instruction Shifts Teacher and Student Interactions During Text‐Based Discussions

Abstract: A B S T R A C TThis study examined how teacher and student interactions were influenced by a multistrategy reading model, Collaborative Strategic Reading (CSR), where students learn to apply before-, during-, and after-reading strategies in small cooperative learning groups. Five middle school English language arts teachers and their students (N = 184) participated as part of a two-year efficacy trial of CSR. Discourse analysis was used to compare the differences in teacher-student talk when the teacher and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 57 publications
0
29
0
3
Order By: Relevance
“…When children have become proficient in decoding, attention should shift toward teaching reading strategies and expanding the children's vocabulary (Pressley et al, 2001;Bimmel and Van Schooten, 2004;Afflerbach et al, 2008). Children should be consistently engaged, but with a gradual shift in responsibility for the success of reading from the teacher to the child (Boardman et al, 2018). This process starts with a teacher demonstrating and explaining his thought processes during reading to serve as a model for children (Schunk, 2003;Afflerbach et al, 2008;Hock et al, 2015).…”
Section: Textbooks and Reading Comprehensionmentioning
confidence: 99%
“…When children have become proficient in decoding, attention should shift toward teaching reading strategies and expanding the children's vocabulary (Pressley et al, 2001;Bimmel and Van Schooten, 2004;Afflerbach et al, 2008). Children should be consistently engaged, but with a gradual shift in responsibility for the success of reading from the teacher to the child (Boardman et al, 2018). This process starts with a teacher demonstrating and explaining his thought processes during reading to serve as a model for children (Schunk, 2003;Afflerbach et al, 2008;Hock et al, 2015).…”
Section: Textbooks and Reading Comprehensionmentioning
confidence: 99%
“…In this study, we focused on one particular aspect of reading instruction that has been emphasized as important across grades (Hougen, ; National Reading Panel [NRP], ), namely, reading comprehension strategies. Although a body of research has shown the effectiveness of strategy instruction for improving reading outcomes (see Boardman, Boelé, & Klingner, ), there has been less research on how teachers frame comprehension strategies in their own classroom teaching. Thus, the ways in which strategies are actually included and taught in modern classroom settings represent a gap in the research.…”
mentioning
confidence: 99%
“…If the text provides explicit evaluation and explanation, and/or students are familiar with the story or topic content, the same question may be less challenging than under other circumstances. Considering different question types and the context in which they are used may also lead to a better understanding of what it means to conduct high-quality teacherstudent interactions (Boardman, Boelé, & Klingner, 2018;Burkins & Croft, 2008;Ford & Opitz, 2008;Frey & Fisher, 2010) that promote students' engagement with the text through initial and follow-up questions that are contingent on students' understanding (Daniel, Martin-Beltrán, Peercy, & Silverman, 2016;McElhone, 2012).…”
Section: Discussionmentioning
confidence: 99%